2008
DOI: 10.1007/s10735-008-9188-8
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and postnatal development in experimental tryptophan deprived rats. A preliminary study

Abstract: An ontogenetic and endocrinological study has been designed on developing rats in uterus of mothers tryptophan deprived at day 1 (exp. 1) and day 14.5 (exp. 2) of conception to verify the supposed determining role of the serotoninergic system (SS) in sexual differentiation in mammals. Tryptophan-free feeding has been pursued uninterruptedly in the litter after birth, during lactation and postnatal development. Tryptophan-free pregnant rats were obtained by exclusion of tryptophan sources from chow. In both exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In mice, the nutritional stress, during the pre-implantation phase, is often responsible of blastocyst death and pregnancy block [4]. Reduction, deprivation or imbalance of nutrients in the very early stages of pregnancy, before implantation, results not only in an obvious impaired somatic development at birth [5,6], but also in the profound alterations of endocrine and metabolic functions [7] and, often, in the impaired maturation of reproductive system in postnatal life [8]. In addition, observations from clinical, epidemiological and experimental studies in vivo and in vitro, showed that different nutrients seem to be able to influence both the normal course of pregnancy and the embryo-fetal development in different animal species, including humans ( Figure 1) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, the nutritional stress, during the pre-implantation phase, is often responsible of blastocyst death and pregnancy block [4]. Reduction, deprivation or imbalance of nutrients in the very early stages of pregnancy, before implantation, results not only in an obvious impaired somatic development at birth [5,6], but also in the profound alterations of endocrine and metabolic functions [7] and, often, in the impaired maturation of reproductive system in postnatal life [8]. In addition, observations from clinical, epidemiological and experimental studies in vivo and in vitro, showed that different nutrients seem to be able to influence both the normal course of pregnancy and the embryo-fetal development in different animal species, including humans ( Figure 1) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, observations from clinical, epidemiological and experimental studies in vivo and in vitro, showed that different nutrients seem to be able to influence both the normal course of pregnancy and the embryo-fetal development in different animal species, including humans ( Figure 1) [1][2][3]. Experimental results showed that undernutrition during pregnancy significantly reduces the number of infants in mice, by increasing the phenomenon of fetal resorption and neonatal mortality [9]; in sheep, it defers intrauterine development of the fetus [10] and in rats, it reduces the weight of pups at birth [8] (Table 1). In case of a severe maternal undernutrition, due to reduced caloric intake, there is a proportional increase in catabolic activity of maternal tissues that results in the release into the maternal-fetal circulation of many amino acids, vitamins and minerals, which are able to balance the insufficient "diet" of the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we investigated the lack of l-Trp, precursor of 5HT, in the diet of pregnant rats to analyse the effects on offspring. We showed impaired growth and development in pups of experimental rats and also alterations in sexual development in growing rats 33 . The most recent literature 31,34 shows the possible negative influence of the excess of 5HT on differentiation of serotonergic neurons of the raphe nuclei in the brainstem; consequently the reduction of pituitary GH production has a direct effect on hepatic production of IGF-I.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 73%
“…Scientific data clearly indicates that the pre-implantation phase is the period of the greatest vulnerability for the future embryo in relation to several endogenous and/or exogenous factors, including nutritional ones [1]. Nutrient reduction, deprivation or imbalance before implantation, could result in somatic hypoevolutism at birth [2], alterations in endocrine and metabolic functions during postnatal life [3] and, often, impaired maturation of the reproductive system [4]. From clinical, epidemiological, and experimental studies, several nutrients seem to influence the regular course of pregnancy and the embryo-foetal development in different animal species, including humans.…”
Section: Introductionmentioning
confidence: 99%
“…From clinical, epidemiological, and experimental studies, several nutrients seem to influence the regular course of pregnancy and the embryo-foetal development in different animal species, including humans. Experimental results in mice have shown that undernutrition in pregnancy significantly reduces the number of puppies, increases the resorption of foetuses and increases neonatal mortality [5]; in sheep, it retards intrauterine development of the foetus [6]; in rats, it reduces the weight of pups at birth [4]. In relation to humans, to evaluate the specific influence of different nutrients on prenatal development is difficult, since a severe maternal undernutrition, with a reduction in caloric intake, will trigger a proportional increase in catabolic activity of the maternal tissues that cause the release in blood, and then in maternal-foetal circulation, of many amino acids, vitamins and minerals that will balance the deficit "diet" of the foetus.…”
Section: Introductionmentioning
confidence: 99%